EFFECT OF AN EQUINE THERAPY PROGRAM ON PSYCHOMOTOR DEVELOPMENT IN CHILDREN BELONGING TO THE SCHOOL INTEGRATION PROGRAM (International Journal of Physiotherapy, 2020)
Background: A large number of children with disabilities exist, who have special educational needs and a delay in psychomotor development; they are frequently incorporated into student integration programs (SIP), forming part of the regular class and receiving complimentary technical and educational assistance. The health system has historically handled these cases through traditional physical therapy; however, currently, other complementary treatment techniques have arisen that produce benefits in the physical, psychological, cognitive, and social aspects of the child. This study aimed to evaluate the impact of an Equine therapy program on the psychomotor development of SIP students.Methods: A quantitative study with a quasi-experimental design and convenience sampling was conducted. Eighteen students (ten men and eight women) from SIP were obtained to establish a control group (N=9) and an experimental group (N=9). The intervention consisted of an 18-weeks program of equine therapy with two sessions each week. Psychomotor development was assessed before and after the intervention with the “Test de Desarrollo y Aprendizaje” (TADI).Results: There was a significant improvement in psychomotor development (p